(untitled) (La U Investiga, 2021)
The health-related quality of life of patients undergoing hemodialysis treatment, complications and compliance with treatment are the elements that will benefit the quality of life of the elderly, these elements must undergo in-depth analysis in order to establish meaningful causal links. Analyzing the quality of life of the elderly patient on hemodialysis by addressing the behavior of the determinants that influence the development of this disease through the application of the KDQOL-36 TM survey, will allow to establish physical, mental and social strategies that allow improving their situation. This quantitative, descriptive, cross-sectional study carried out at the Ambato General Hospital IESS was carried out with a non-probabilistic sampling for the author’s in a universe of 35 patients, the “Quality of Life” questionnaire was applied with the purpose of knowing the personal characteristics of these patients with chronic renal failure on hemodialysis. The KDQOL-36TM instrument (items 13-36) was applied to evaluate the patient with health problems, finding that their quality of life is lower compared to a healthy individual, hemodialysis patients present a medium-low quality of life and affected area is physical, These is a greater link with social relationships since the better the social relationship, the better quality of life according to the patient’s perception. On the other hand, the limitations of the disease disturb relations with his circle of friends and with his relatives.